The mosaic evolution of Left Dislocation in Xhosa - Andrason, Alexander; Visser, Marianna W. (Stellenbosch Papers in Linguistics Plus, 2016)
This paper demonstrates that the status of Clitic LD in Xhosa is a result of the mosaic evolution of Xhosa grammar. It emerges as an accumulation and combination of two more individual, distinct and, at least, initially separated developments and characteristics – LD sensu stricto and Object Agreement. This view enables the authors to propose a possible solution to the problem of whether the Clitic LD structure in Xhosa (and Nguni) is an instantiation of LD (and its prototypical function as posited by Westbury (2014)) or fronting (and its topical and focal functions). The Clitic LD structure is employed to accomplish the two tasks. The former is derived from the original LD construction, while the latter arose due to the Object Agreement cycle. The mosaic character of LD in Xhosa, in turn, demonstrates the situatedness of LD. LD is determined not only by its own evolutionary baggage (the source from which it has developed) but also by the dynamics of the environment in which it has been embedded (the properties of other constructions).